Systematic experimental assessment of a 2D-motion sensor to detect relative movement between residual limb and prosthetic socket - Noll, Veronika; Rinderknecht, Stephan; Beckerle, Philipp (Sensors, 2018)
A sensor system for measuring the relative movement between prosthetic socket and residual limb based on a 2D-motion sensor is introduced and thoroughly tested experimentally. The quantitative analysis of test rig evaluation is used to identify advantageous sensor settings and liner configurations. Considering these favorable settings, sensor functionality is quantified to errrel = 0.52 ± 1.78%. Advancing to convex measurement surfaces, the sensor shows absolute errors of errabs ≤ 1 mm in an observable measurement scenario. The feasibility of measuring gait-induced relative movement with the proposed 2D-motion sensor is shown via a biomechanical plausibility study. Overall, the findings suggest that the proposed sensor system is suitable for investigating the relative movement between residual limb and prosthetic socket in dynamic gait situations.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Biomechanical measurement tasks; Gait analysis; Lower limb prosthetics; Quantifying socket fit; Relative movement